2021
DOI: 10.1371/journal.pgen.1009708
|View full text |Cite
|
Sign up to set email alerts
|

Ras/ERK and PI3K/AKT signaling differentially regulate oncogenic ERG mediated transcription in prostate cells

Abstract: The TMPRSS2/ERG gene rearrangement occurs in 50% of prostate tumors and results in expression of the transcription factor ERG, which is normally silent in prostate cells. ERG expression promotes prostate tumor formation and luminal epithelial cell fates when combined with PI3K/AKT pathway activation, however the mechanism of synergy is not known. In contrast to luminal fates, expression of ERG alone in immortalized normal prostate epithelial cells promotes cell migration and epithelial to mesenchymal transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…By applying functional annotation on a network, they find Ras protein signal transduction is one of the important signaling pathways in prostate cancer. Also in 2021, Strittmatter et al [ 32 ] show the change in ERG expression gene by Ras/ERK and PI3K/AKT signaling pathways, promoting prostate tumor.…”
Section: Resultsmentioning
confidence: 99%
“…By applying functional annotation on a network, they find Ras protein signal transduction is one of the important signaling pathways in prostate cancer. Also in 2021, Strittmatter et al [ 32 ] show the change in ERG expression gene by Ras/ERK and PI3K/AKT signaling pathways, promoting prostate tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Ras is an important protein that links PI3K/MAPK signaling [32]. Ras is overexpressed in many cancers and is involved in cancer growth and metastasis through the activation of PI3K/MAPK, making it a potential target for cancer therapy [33]. Ras is known to activate ERK1/2 in the MAPK signaling pathway [34], and it is therefore suggested that the reduction of Ras expression by nanaomycin K may be one of the mechanisms by which it inhibits the activation of the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the RAS-ERK signaling pathway has been increasing in recent years. For example, tumorigenic Sergi-mediated transcription in prostate cells could be adjusted by RAS-ERK and PI3K-AKT signaling pathways differentially [33]. Vemurafenib significantly reduced the proliferation of melanocyte nevus by targeting the RAS-ERK pathway [34].…”
Section: Discussionmentioning
confidence: 99%